Sosialisasi Pencegahan Hoax dan Ujaran Kebencian di Madrasah Aliyah Swasta Muhammadiyah Bayongbong - Eri Satria; Agil Rahmat; Zatnika Insan Kamil; Muhammad Alfi Faishal; Gina Suciyana; Garnis Kirani (Journal of Community Development, 2024)
Hate speech and hoaxes have become significant problems in the current era of democracy and digitalization. Advances in Information and Communication Technology (ICT), especially social media, have facilitated the rapid and widespread spread of hoaxes and hate speech in Indonesia. The main problem in dealing with hoaxes is the lack of critical thinking about the information received. Therefore, prevention of hoaxes through education is important. Education can help people detect hoax news and reduce its spread. To conduct this education, the research method used is socialization and education at MAS Muhammadiyah Bayongbong school, especially at the high school level. This activity involved students, partners, and participants. The stages of the activity include surveys, delivery of material on hoaxes and education, and practice using ICT. This activity showed that some participants experienced an increase in knowledge after participating in the socialization. However, there were some difficulties in answering the test questions given. In addition, analysis of the average score of the questions showed an increase from pre-test to post-test. However, there are some materials that are still an obstacle for participants in understanding them.